Fish-borne trematode infections in wild fishes in Bangladesh. (17th February 2020) - Labony, Sharmin S.; Alim, M. Abdul; Hasan, Muhammad Mehedi; Hossain, Md. Shahadat; Islam, Ausraful; Alam, Mohammad Zahangir; Tsuji, Naotoshi; Anisuzzaman,
ABSTRACT: Fish-borne liver and intestinal flukes are helminth pathogens that have a negative impact on public health worldwide. We herein investigated the status of infection by the metacercariae (MC) of fish-borne trematodes (FBTs) in randomly selected freshwater wild fishes. Five species of fishes were collected and digested artificially using digestion fluid to recover MC. All fish species, namely, ticto barb ( Puntius ticto ) (14/16, 87.5%), banded gourami ( Colisa fasciata) (8/12, 66.7%), freshwater garfish ( Xenentodon cancila ) (9/14, 64.3%), flying barb ( Esomus danricus ) (5/12, 41.7%), and reba carp ( Cirrhinus reba ) (7/11, 63.7%), were infected with FBTs. The overall infection rate was 66.2% and the mean intensity was 748.3 ± 2947.5 MC/100 g of fishes. The loads of MC in ticto barb, reba carp, freshwater garfish, banded gourami, and flying barb per 100 g of fishes were 1978.8 ± 5053.7, 268.3 ± 440.7, 140 ± 105.4, 134.3 ± 109.2, and 117.6 ± 102.3, respectively. The infection rate was significantly higher (P < 0.05) in the body (55.4%) than in the head (40%) of fishes. Morphological and morphometrical analyzes identified the MC of Clonorchis spp., Opisthorchis spp., Metorchis spp., Metagonimus spp., and Echinostoma spp. Collectively, the present results suggest that wild freshwater fishes are important intermediate hosts for FBTs, and play a critical role in the transmission cycle of these parasites in Bangladesh. The results also indicate that people of the country are at risk of these infections.